Production of high-purity indium and gallium metals by vacuum refining - Lee, MS; Ahn, JG; Oh, YJ (JAPAN INST METALS, 2002)
Vacuum refining experiments of indium and gallium metals have been performed. When indium metal of 99.97% purity was refined at 1273 K and 1.3 x 10(-3) Pa for one hour, Pb and Bi were effectively removed from indium metal. After refining 99.9% Ga at 1373 K and 1.3 x 10(-3) Pa for six hours, removal of Bi, Pb, Zn, Mg, Ca and Fe were confirmed. The difference of temperature between indium and gallium at which the recovery percentage was abruptly decreased was related to the difference of boiling temperatures of both metals at the pressure of 1.3 x 10(-3) Pa. The vaporization rate of solvent metals obtained from experiments were compared with those calculated by Langmuir equation.